Colonic Intramural Hematoma in a Cat: A Case Report - Hsu, Ti-Chiu; Lin, Lee-Shuan; Chung, Cheng-Shu; Chiang, Chuan; Chiu, Hsien-Chieh; Huang, Ping-Hsun (Frontiers in Veterinary Science, 2022)
Colonic intramural hematoma is a rare condition in humans and companion animals. Its clinical presentation in cats has not previously been reported. An 8-year-old male American shorthair cat presented with acute onset of constipation and anorexia for 3 days. Laboratory examination indicated mild elevation of alanine aminotransferase, globulin, and total protein levels. Complete blood count was normal. Radiographs revealed a soft tissue opacity mass located caudodorsally to the urinary bladder, causing narrowing of the descending colonic lumen. Sonography showed a heteroechogenic intraluminal mass containing liquefied content between the submucosal and muscular layers of the descending colon. On computed tomographic images, the mass contained two different attenuated contents with an interface. Colonoscopy was then performed for intestinal biopsy, and the contents observed in the intraluminal mass were drained via surgical evacuation and considered as blood clots. Supportive medical treatment, including antibiotics and fecal softener, was administered, and the clinical signs resolved uneventfully. Mild chronic proctitis without apparent malignancy was confirmed histopathologically, and no recurrence was observed after more than 14 months, and thus a colonic intramural hematoma was presumptively diagnosed. The information provided by multimodal imaging of the mass was essential for the diagnosis and determination of the treatment in this case.